Exome sequencing identifies DYNC2H1 mutations as a common cause of asphyxiating thoracic dystrophy (Jeune syndrome) without major polydactyly, renal or retinal involvement - ELÇİOĞLU, HURİYE NURSEL (BMJ PUBLISHING GROUP, 2013)
Background Jeune asphyxiating thoracic dystrophy (JATD) is a rare, often lethal, recessively inherited chondrodysplasia characterised by shortened ribs and long bones, sometimes accompanied by polydactyly, and renal, liver and retinal disease. Mutations in intraflagellar transport (IFT) genes cause JATD, including the IFT dynein-2 motor subunit gene DYNC2H1. Genetic heterogeneity and the large DYNC2H1 gene size have hindered JATD genetic diagnosis. Aims and methods To determine the contribution to JATD we screened DYNC2H1 in 71 JATD patients JATD patients combining SNP mapping, Sanger sequencing and exome sequencing. Results and conclusions We detected 34 DYNC2H1 mutations in 29/71 (41%) patients from 19/57 families (33%), showing it as a major cause of JATD especially in Northern European patients. This included 13 early protein termination mutations (nonsense/frameshift, deletion, splice site) but no patients carried these in combination, suggesting the human phenotype is at least partly hypomorphic. In addition, 21 missense mutations were distributed across DYNC2H1 and these showed some clustering to functional domains, especially the ATP motor domain. DYNC2H1 patients largely lacked significant extra-skeletal involvement, demonstrating an important genotype-phenotype correlation in JATD. Significant variability exists in the course and severity of the thoracic phenotype, both between affected siblings with identical DYNC2H1 alleles and among individuals with different alleles, which suggests the DYNC2H1 phenotype might be subject to modifier alleles, non-genetic or epigenetic factors. Assessment of fibroblasts from patients showed accumulation of anterograde IFT proteins in the ciliary tips, confirming defects similar to patients with other retrograde IFT machinery mutations, which may be of undervalued potential for diagnostic purposes.
Keywords: RETROGRADE INTRAFLAGELLAR TRANSPORT; PRIMARY CILIARY DYSKINESIA; LIGHT INTERMEDIATE CHAIN; DYNEIN MOTOR DOMAIN; PELVIC-PHALANGEAL DYSTROPHY; CYTOPLASMIC DYNEIN; CRYSTAL-STRUCTURE; CAENORHABDITIS-ELEGANS; DEFECTS; IFT